PEMANFAATAN MULTIMEDIA MENGGUNAKAN GOOGLE SITES BAGI GURU-GURU SMP SMK PUTRA SATRIA SEBAGAI MEDIA PEMBELAJARAN JARAK JAUH - Suharto, Agus (Pondok Jurnal-LP2M STAI Darul Kamal, 2021)
Teachers and staff in carrying out their duties cannot be separated from the use of information technology, in several schools including partner schools, namely SMP & SMK PUTRA SATRIA. there are still many teachers and TU staff who are not familiar with the use of information technology. For this reason, it is necessary to increase skills through training in the use of Google application information system software. This activity is carried out in 3 stages, namely the preparation stage, then the Distance Learning training stage with Google Sites, Google Classroom, then the effectiveness evaluation stage with questionnaires by participants, Based on the data obtained from the questionnaire via google form about the effectiveness of distance learning using the Google Sites platform, google classroom, as follows very ineffective 7%, ineffective 10%, quite effective 10%, effective 67%, very effective 7%